2020
DOI: 10.1055/a-1302-2942
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking definitions of false-positive alerts during computer-aided polyp detection in colonoscopy

Abstract: Introduction The occurrence of false positive (FP) alarms is an important outcome measure in computer-aided colon polyp detection (CADe) studies. However, there is no consensus definition for FPs in clinical trials evaluating CADe in colonoscopy. We aimed to study the diagnostic performance of CADe based on different threshold definitions for FP alarms. Methods A previously validated CADe system was applied to screening/surveillance colonoscopy videos. Different thresholds for FP alerts were defined based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 10 publications
0
22
1
Order By: Relevance
“…This positive correlation raised questions about the conclusion that FPs had no clinical impact [ 12 ]. Another study analyzing FPs also found that a higher number of FPs was associated with longer withdrawal time ( Table 4 ) [ 13 ]. It appears that FPs did contribute to a longer withdrawal time, but that the impact might be quite limited by the commercially available system and experienced endoscopists.…”
Section: Adverse Effects Of Fpsmentioning
confidence: 99%
See 4 more Smart Citations
“…This positive correlation raised questions about the conclusion that FPs had no clinical impact [ 12 ]. Another study analyzing FPs also found that a higher number of FPs was associated with longer withdrawal time ( Table 4 ) [ 13 ]. It appears that FPs did contribute to a longer withdrawal time, but that the impact might be quite limited by the commercially available system and experienced endoscopists.…”
Section: Adverse Effects Of Fpsmentioning
confidence: 99%
“…False positives have various definitions across different studies ( Table 1 ). In general, the term refers to computer prompts indicating polyps that the endoscopist does not consider to be polyps [ 12 , 13 ]. Some investigators have used false alarms to define tracking boxes on non-polyp structures that were continuously tracked [ 7 , 8 ], while other authors ignored brief false positives [ 4 , 12 ].…”
Section: Definition Of False Positivesmentioning
confidence: 99%
See 3 more Smart Citations